Analisis Pemilihan Strategi Pembelajaran Dalam Mendorong Sikap Responsif Siswa Pada Proses Belajar Matematika Materi Integral Parsial - Aisyah Rose Faidina; Fevni Dian Pitaloka; Wardah Nur Syamsiyah; Ul’fah Hernaeny (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This article is the result of a literature study regarding appropriate learning strategies for various student characteristics for the teaching and learning process in Mathematics subjects, especially integral calculus material. The problem analysis will focus on three things, including (1) Comparison between expository learning strategies and differentiation learning in Mathematics material; (2) The influence of learning strategy selection on students' interest in learning in integral calculus material; and (3) The influence of learning interest on students' mathematics learning outcomes in integral calculus material. The purpose of writing the article is to provide an educational overview regarding the importance of an educator's understanding of the diversity of abilities possessed by their students, as well as selecting appropriate learning models or strategies to increase students' responsive attitudes. The results obtained in writing articles after the literature study process are that describing appropriate learning strategies in the teaching and learning process will increase responsiveness, because direct interaction between teaching staff and their students is one of the important aspects that must be considered in the learning process, as well as encouraging a sense of students want to know. The research in this article uses qualitative literature study methods. Data was obtained from various written reference sources, both from journals and articles.